Effect of lncRNA RMRP on proliferation, apoptosis, osteoblast differentiation and mineralization of bone marrow mesenchymal stem cells - Jingyuan Guo; Yiwang Man; Shuai Xiang; Xiaomei Zhong; Genyun Tang; Jiefu Tang (Russian Open Medical Journal, 2025)
Background — Long non-coding RNAs (lncRNAs) play a crucial role in bone growth and skeletal development. Ribonuclease (RNase) for mitochondrial RNA processing, commonly known as RMRP, is a small nucleolar ribonucleoprotein particle composed of RMRP lncRNA (lncRNA RMRP) and several protein subunits. Specifically, mutations in lncRNA RMRP are associated with cartilage-hair hypoplasia and skeletal developmental disorders in humans. For instance, mutations in lncRNA RMRP are observed in individuals with severe dwarfism, thus suggesting that RMRP functions in both chondrogenic and osteogenic processes. Results of a previous study have identified a potential role of RMRP in chondrogenic differentiation in mouse cell lines. However, the specific functions of RMRP in osteogenic processes remain unclear. Methods — In the present study, RMRP expression was altered in murine bone marrow derived mesenchymal stem cells (BMSCs). Reverse transcription-quantitative polymerase chain reaction (RT-qPCR), cell counting, apoptosis and mineralization assays were used to investigate the effects of RMRP on BMSCs, osteoblasts and osteogenic differentiation. Results — The results of the present study showed that RMRP expression was up-regulated in BMSCs and down-regulated during apoptosis. The RMRP knockdown resulted in decreased proliferation and viability of BMSCs and increased apoptosis. In addition, the RMRP knockdown increased osteoblast differentiation of BMSCs and affected the mineralization of osteoblastic cells. Conclusion — The results of the present study indicated that RMRP may play a role in BMSCs, osteoblastic cells and osteogenic differentiation process. Therefore, the present study may provide a new theoretical basis for the role of RMRP in skeletal development.